New classification of osteochondral lesions of the talus in adults - Batista, Jorge; Matías-Joannas, Germán; Casola, Leandro; Logioco, Lucas; Arrondo, Guillermo (Journal of the Foot & Ankle, 2021)
Osteochondral lesions (OCL) of the ankle in adults are frequent lesions that mainly affect the cartilage and the subchondral bone, are relatively common, and have varied etiologies. However, in 50% of patients, these lesions may occur concomitantly with chronic instability of the ankle associated with lower limb deformities, acute sprains of the ankle, or fractures. We propose a classification into four types of lesions (traumatic, non-traumatic, with lateral instability of the ankle, and with mechanical axis defects), focusing not only on the diagnosis and treatment of OCL but also on associated injuries, such as instability and/or supramalleolar and hindfoot deformities. Level of Evidence V; Therapeutic Studies; Expert Opinion.